Upaya Meningkatkan Pemahaman Konsep Materi Keberagaman Menggunakan Media Secret Box di Sekolah Dasar Negeri 066055 Medan - Fitria, Husnul; Ammy, Putri Maisyarah; Simatupang, Mesli (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2025)
This study explores the effectiveness of using Secret Box media to enhance fourth-grade elementary school students’ understanding of diversity-related concepts. The research was motivated by the low level of student comprehension, as evidenced by initial learning evaluation results showing a mastery rate of only 33%. Employing a classroom action research (CAR) approach, the study was conducted in two cycles at UPT SDN 066055 Medan. In the first cycle, the implementation of media was suboptimal, resulting in a moderate increase in learning completeness to 67%. To address this, the second cycle involved the integration of Secret Box media with supporting instructional videos, leading to a significant improvement in student outcomes. Final assessments showed that 92% of students achieved mastery. The findings indicate that Secret Box media not only facilitates better understanding of diversity content but also fosters active engagement, enthusiasm, and curiosity among students during the learning process. This study concludes that creative and contextual learning tools like the Secret Box can effectively bridge conceptual gaps in elementary classrooms, particularly in abstract thematic subjects such as social diversity.